Autologous CD34+ Cell Therapy for Refractory Angina: 2-Year Outcomes from the ACT34-CMI Study. Issue 9 (September 2016) - Henry, Timothy D.; Schaer, Gary L.; Traverse, Jay H.; Povsic, Thomas J.; Davidson, Charles; Lee, Joon Sup; Costa, Marco A.; Bass, Theodore; Mendelsohn, Farrell; Fortuin, F. David; Pepine, Carl J.; Patel, Amit N.; et al.
An increasing number of patients have refractory angina despite optimal medical therapy and are without further revascularization options. Preclinical studies indicate that human CD34 + stem cells can stimulate new blood vessel formation in ischemic myocardium, improving perfusion and function. In ACT34-CMI ( N = 167), patients treated with autologous CD34 + stem cells had improvements in angina and exercise time at 6 and 12 months compared to placebo; however, the longer-term effects of this treatment are unknown. ACT34 was a phase II randomized, double-blind, placebo-controlled clinical trial comparing placebo, low dose (1 × 10 5 CD34/kg body weight), and high dose (5 × 10 5 CD34/kg) using intramyocardial delivery into the ischemic zone following NOGA ® mapping. To obtain longer-term safety and efficacy in these patients, we compiled data of major adverse cardiac events (MACE; death, myocardial infarction, acute coronary syndrome, or heart failure hospitalization) up to 24 months as well as angina and quality of life assessments in patients who consented for 24-month follow-up. A total of 167 patients with class III–IV refractory angina were randomized and completed the injection procedure. The low-dose-treated patients had a significant reduction in angina frequency ( p = 0.02, 0.035) and improvements in exercise tolerance testing (ETT) time ( p = 0.014, 0.017) compared to the placebo group at 6 and 12 months. At 24 months, patients treated with both low-and high-dose CD34 + cells had significant reduction in angina frequency ( p = 0.03). At 24 months, there were a total of seven deaths (12.5%) in the control group versus one (1.8%) in the low-dose and two (3.6%) in the high-dose ( p = 0.08) groups. At 2 years, MACE occurred at a rate of 33.9%, 21.8%, and 16.2% in control, low-, and high-dose patients, respectively ( p = 0.08). Autologous CD34 + cell therapy was associated with persistent improvement in angina at 2 years and a trend for reduction in mortality in no-option patients with refractory angina.